Penerapan Program SATAMPAH (Saluran Tanpa Sampah) sebagai Pencegahan Stunting Melalui Pembersihan Sanitasi Di Kelurahan Debong Kidul, Kabupaten Tegal: Implementation SATAMPAH (Saluran Tanpa Sampah) Program as Stunting Prevention Through Sanitation Cleaning in Debong Kidul Village, Tegal Regency - Kurniawan, Muhammad Hendri; Sarwadhamana, Raden Jaka; Arifianto, Budi; Suryani, Lilis; Hasna, Zulfa Nadila; Pitriani, Dia; Sakti, Ali Zulfa Rois Arifa; Hoyyar, Mohammad; Maulani, Adinda Diar; Wulandari, Sinta; Lestari, Okti Dewi; Hikmah, Septiana Nur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Stunting is a key indicator of inadequate nutrition in children, and the role of healthy sanitation in preventing stunting is a focus of attention. Tegal Regency's stunting rate was reduced by 6.5 percentage points, from 22.3 percent in 2022 and 21.5 percent in 2023 Efforts in sanitation management, the Tegal Government rejected the SATAMPAH Program which is the implementation of a clean sanitation cleaning program with Debong Kidul residents, 1). Observation. 2) Coordination. 3) Physical activity, 4) Through the SATAMPAH program, Debong Kidul urban village has carried out good stunting prevention in its implementation, and residents in the Debong Kidul environment are very enthusiastic about working together. Sanitation in Debong Kidul Village still requires community involvement, namely to always keep the sanitation environment clean and increase the prevention of stunting in the future. SATAMPAH has been able to increase awareness and knowledge at the community level regarding the relationship between proper sanitation and stunting prevention. The implementation of this program is expected to be an effective version for various regions in reducing stunting rates while supporting the national target of reducing stunting in Indonesia. Continuous assessment of the impact of this implementation is needed to ensure its sustainability and effectiveness over time.